Assessing Teacher's Beliefs and Practices in relation to the Integration of Grammar and Reading in Foreign Language Teaching in Secondary Schools in Ethiopia - Chali, Gemechis T.; Mouvet, Kimberley; Taverniers, Miriam (Afrika Focus, 2020)
Studies have suggested that teachers’ beliefs have a significant influence in language teaching (e.g., Williams and Burden, 1997), i.e. that teachers’ beliefs will significantly influence their teaching practice. This study examines teachers’ beliefs and practices in relation to the integration of grammar and reading in foreign language teaching. A qualitative research design with Focus Group Discussion (FGD) and observation data gathering tools was employed. The study revealed that teachers hold positive beliefs on teaching grammar and reading in an integrated way, but their beliefs were not reflected in the classroom. The key finding of this paper was that teachers strongly believed in the usefulness of the integration of grammar and reading, but there were difficulties to reflect it in practice. This paper suggests that an alternative technique should be developed on discrete ways of teaching to allow teachers to practise their beliefs either on the existing text or through adapting the textbook. The findings of the study may have important implications for EFL (English as a Foreign Language) teachers and practitioners. KEY WORDS: TEACHERS’ BELIEFS, TEACHING GRAMMAR AND READING, PRACTICES, INTEGRATED TEACHING